Investigations of burning phenomena during the hard anodising of aluminium by local in-operando temperature measurements. (20th September 2017) - Lämmel, C.; Schneider, M.; Heubner, C.; Beckert, W.; Michaelis, A.
Highlights: Local in-operando temperature measurements during anodising and burning. Calculation of local thermo-mechanical stress inside the oxide using CLPT. Local temperatures and stress inside the oxide rise up to 140 °C and 730 MPa. Varying oxide morphologies depending on the local anodising conditions. Recurrent formation and relaxation of stress inside the oxide during burning. Abstract: The heat evolution during hard anodising in sulfuric acid with and without provoked burning is investigated using an in-house designed setup for local in-operando temperature measurements. Local heat flows are computed from the measurements and compared to the average Joule heating and the heat flow into the electrolyte. The development of temperature gradients during the anodization process and burning is discussed in view of the formation of thermo-mechanical stress and its influence on the properties and microstructure of the resulting oxide layer. Comprehensive SEM-mapping of the sample surface subjected to burning is performed and the results are analysed regarding the local temperatures as well as thermo-mechanical stress effects during anodising.